Implementasi Kode Etik Jurnalistik di Media Televisi Studi Deskriptif Penerapan Pasal 7 Tentang Hak Narasumber Di Metro TV - Firmansyah Firmansyah; Sani Rahman; Chotijah Fanaqi (Journal on Education, 2024)
This research is undermined by the code of ethics applied in Metro TV television media in particular article 7 on source rights, the content of which is that Indonesian journalists have the right to protect sources who do not want to know their identity and existence, respect the provisions of the embargo, background information and off the record. Which, after researchers observed the Metro TV media, Metro TV applied a good journalistic code of ethics especially in chapter 7. The aim of this study is to explain the implementation of the journalistic ethics code on Metro TV in applying chapter 7 on source rights in the dimensions of leadership, justice, honesty, and courage. The research methods used are qualitative descriptive methods with virtue ethics theory according to Aristotle and After Virtue theories according to Alasdair Maclntyre. Data collection techniques used are observations, interviews and documentation. This research focuses on researching the elements of leadership, justice, honesty and courage. The investigators took two active Metro TV reporters, two sources, one Kompas TV reporter and one deputy chairman of KPID Jabar. The results of this research show that the dimensions of leadership, justice, honesty and courage are as follows. The dimension of leadership is that Metro TV must have a leadership role in order to enhance a good media reputation. The last dimension of courage is that Metro TV reporters must be brave in dealing with a controversial report.